2016
DOI: 10.18276/os.2016.3-02
|View full text |Cite
|
Sign up to set email alerts
|

Care for the Parents’ Generation in the Process of Migration in the Opinions of Polish Female Migrants in Norway and of Social Workers and Priests in Poland

Abstract: WprowadzenieNie sposób przecenić roli, jaką odgrywa rodzina, ale też nie sposób nie dostrzec jej wyzwań i dylematów, jakie przeżywa w ostatnich kilku dekadach. Patrząc na jej rolę, trzeba podkreślić, po pierwsze, że nie tylko daje życie, lecz także na podstawie więzi pokrewieństwa i więzi emocjonalnych oraz sieci wzajemnych zobowiązań, świadczeń i zależności zapewnia lub dąży do zapewnienia jednostce w miarę satysfakcjonujących warunków bytowych, rozwoju osobowego i społecznego, przy czym za jeden z warunków i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A number of demographic studies conducted by various authors have shown that both in Poland and other countries in the world the number of women in older age groups is significantly growing [9,5,10]. Following the statistical data, women more often live alone and assess their health condition as worse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of demographic studies conducted by various authors have shown that both in Poland and other countries in the world the number of women in older age groups is significantly growing [9,5,10]. Following the statistical data, women more often live alone and assess their health condition as worse.…”
Section: Discussionmentioning
confidence: 99%
“…The author draws attention to the difference between the highest pension paid by Social Insurance Company (ZUS) and Farmer's Social Security Fund (KRUS), which in 2009 totalled 765 PLN, which indicates that retirees in rural areas have much lower financial resource [2]. The disabled elderly living in rural areas experience various barriers and limitations [2][3][4], generally resulting from inappropriate infrastructure, personal social care and difficult financial situation [5,6]. The scattered location of the housing causes that seniors living in rural areas experience troubles with shopping and access to cultural assets [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…A factor that led to the intensification of feminisation of migration was changes in the family welfare capital in highly developed countries. Low fertility rates, better accessibility and development of education resulting in increased female labour force participation, as well as a growing number of people in the post-working age and ageing populations, have led to a large increase in demand for care services (Cangiano, 2014;Kawczyńska-Butrym, 2014). One frequently used solution to cope with this situation is the employment of immigrant women in households (Matuszczyk, 2019).…”
Section: Contemporary Migration Of Women In the World And In Europementioning
confidence: 99%
“…Young adults have knowledge about the negative impact of risky behaviours and, at the same time, they are fully aware of the fact that they underestimate the possible consequences [ 20 ]. The research by Andruszkiewicz et al [ 21 ] shows that highly motivated people have a significantly higher global sense of understandability of the rationale for limiting health risk activities than people with low motivation.…”
Section: Introductionmentioning
confidence: 99%